Statutory nuisance and residential property : environmental health problems in housing - Battersby, Stephen, 1949-; Pointing, John (Abingdon, Oxon ; New York, NY : Routledge, 2019)
Statutory Nuisance and Residential Property: Environmental Health Problems in Housing examines the statutory nuisance provisions in the Environmental Protection Act 1990 pertaining to the condition of premises and related problems in housing and compares these with the provisions of the Housing Act 2004. The book discusses the separate development of statutory nuisance and housing legislation in an historic context, which provides a useful basis for the understanding and interpretation of legislation and the different remedies available today. The work includes a chapter on actions by "persons aggrieved "using section 82 of the Environmental Protection Act 1990 and also considers remedies provided in the Anti-social Behaviour, Crime and Policing Act 2014. This book: investigates housing problems in the context of the relevant law; and demonstrates how to use the legal framework appropriately and be able to decide on the most appropriate provision for dealing with environmental health problems associated with residential property. This is an essential and practical book for environmental health and housing professionals, as well as for advisers and lawyers in the private and public housing sectors.
Introduction -- Historical development of statutory nuisance -- Development of the law on housing conditions (housing legislation) -- The law of nuisance and statutory nuisance -- Procedural and practice issues under the Housing Act 2004 -- Procedural and practice issues for statutory nuisance -- Other remedies, powers and related actions -- Resolving problems with residential property -- Case studies.
OCLC-licensed vendor bibliographic record.
Keywords: Housing -- Law and legislation -- England; Nuisances -- England; Housing and health -- England; Housing -- Environmental aspects -- England; LAW / Administrative Law & Regulatory Practice; LAW / Housing & Urban Development; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development; SOCIAL SCIENCE / Sociology / Urban